Panorama de algunas representaciones sobre el conflicto armado interno en el cine peruano - Bedoya Wilson, Ricardo (2024)
This text offers a panoramic view of some of the representations of the internal armed conflict offered by Peruvian cinema from the end of the 1980s to the present day. By mentioning some emblematic titles, we point out the coincidences and divergences shown in the cinematographic perspectives and treatments of political violence in Peru over the years.